Identification of Influential Attribute for Prioritizing Wall Material Selection in Low-Cost Housing - Wahyu Ari Pramono; Setya Winarno; Sri Kusumadewi; Fitri Nugraheni (Universitas Islam Raden Rahmat, Malang, 2026)
Selecting appropriate wall materials for low-cost housing is a complex decision-making process involving multiple technical, economic, social, and environmental considerations. This study aims to identify and prioritize the most influential attributes affecting wall material selection for affordable housing. A total of twenty-two attributes were derived from a comprehensive literature review and evaluated through a structured questionnaire survey involving 30 respondents, consisting of academics, decision-makers, and technical practitioners. A consensus-based weighting approach was applied using the mean value (μᵢ), normalized weight (wᵢ), and relative ratio (r) to establish the priority structure of attributes. The results indicate that all attributes are considered relevant (r > 0.1), with the highest priorities assigned to structural strength and stability (T1, w = 0.060), initial wall cost (E1, w = 0.058), life-cycle cost (E2, w = 0.057), durability and weather resistance (T3, w = 0.056), occupant safety and perceived security (S4, w = 0.056), and embodied carbon and energy (L1, w = 0.053). At the aspect level, technical factors contributed 34% of the total weight, followed by economic (26%), social (21%), and environmental aspects (19%). These findings provide a quantitative attribute-weighting framework that can support the development of Multi-Attribute Decision Making (MADM) models for context-sensitive wall material selection in low-cost housing.